Case report of adrenocortical carcinoma associated with double germline mutations in MSH2 and RET. Issue 4 (21st February 2021) - Raygada, Margarita; Raffeld, Mark; Bernstein, Andrew; Miettinen, Markku; Glod, John; Hughes, Marybeth S.; Reilly, Karlyne; Widemann, Brigitte; Del Rivero, Jaydira
ABSTRACT: Adrenocortical carcinoma (ACC) is a rare aggressive malignancy that originates in the outer layer of the adrenal gland. Most ACCs are sporadic, but a small percentage of cases are due to hereditary cancer syndromes such as Li‐Fraumeni syndrome (LFS), Lynch syndrome (LS), and familial adenomatous polyposis (FAP). Multiple endocrine neoplasia type 2A (MEN2A) is an inherited disorder that predisposes to medullary thyroid cancer, pheochromocytoma, and parathyroid hyperplasia. We present here a case of ACC with both LS and MEN2A; the family and medical history were consistent with Lynch. This is, to our knowledge, the first report of a patient with ACC associated with germline mutations in RET and MSH2, and no phenotypical characteristics of MEN2A.